Work Engagement Among Indonesian National Police Officers: A Descriptive Study Based on Demographic Characteristics - Firizki Annisa Putri; Umi Anugerah Izzati; Olievia Prabandini Mulyana (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Work engagement is a positive psychological state characterized by vigor, dedication, and absorption. This study aimed to describe the level of work engagement among Indonesian National Police officers. A quantitative descriptive design was employed using purposive sampling. Participants consisted of 127 police officers from a regional police department in Indonesia. Data were collected using the Utrecht Work Engagement Scale-9 (UWES-9), adapted into Indonesian by Kristiana et al. (2018). The scale demonstrated acceptable reliability (Cronbach’s α = .760), and all items were found to be valid (p < .05). Data were analyzed using descriptive statistics, including mean, standard deviation, and categorization analysis. Results showed a mean work engagement score of 47.87 (SD = 4.86). Most participants were categorized as having high work engagement (56.7%), followed by moderate (20.5%), low (15.0%), and very low (7.9%) levels. These findings indicate that police officers generally exhibit high levels of work engagement.